MENOPAUSE: A NEGLECTED REPRODUCTIVE HEALTH CONCERN IN CAMEROON - Fomulu, J.N; Bechem, E; Nkwabong, E; Nana, P.N (HEALTH SCIENCES AND DISEASE, 2013)
Introduction: Menopausal medicine is an outstanding problem in health care systems in Africa as a whole and in Cameroon in particular. Most menopausal women tend to seek medical attention in various medical specialties because of the polymorphous clinical features of menopause, yet its origin is gynaecological. This may be due to the lack of knowledge on menopause by health practitioners and decision makers. Methods: In this complete literature review, we carried out a meta analysis of menopause through its definition, age of onset, pathophysiology, clinical presentation, complications, diagnosis and management. Conclusion: Adequate provision of knowledge to medical practitioners and decision makers on this natural ageing phenomenon with emphasis on the creation of menopausal clinics as an integral part of reproductive health delivery system appears necessary for the appropriate management of the many menopausal women in Cameroon.